The Effect of Problem Based Learning Model on Critical Thinking Skills in Elementary School: A Meta Analysis Study - Halimatus Sa'diyah; Umalihayati; Ratna Hidayah; Moh Salimi; Laksmi Evasufi Widi Fajari; Mashudi; Syarifah Aini (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2024)
Critical thinking was an essential skill that must be taught from elementary school to address the challenges of problem-solving in the development of science and technology. Critical thinking skills of the 21st century could be developed by applying the Problem Based Learning model. The article aimed to test the validation of the effect of the Problem Based Learning model on the critical thinking skills of elementary school students in Indonesia. The research method used quantitative meta-analysis method that was assisted by JASP 0.8.5 software. Research data used with eligibility criteria, including: (1) publications could be traced in Google Scholar, (2) publications are only indexed by SINTA, (3) publications must be related to the topic, (4) publication subjects must be at the elementary school level, (5) publications results from Indonesia, (6) publications include (r), (t) or (F) values, (7) publications must be published in the range of 2014 to 2022, (8) publications must have N ≥ 20. The results showed that in 25 research articles, there was a significant effect of applying the Problem Based Learning model on the critical thinking skills with a strong category. It contributed on problem-based learning model has a significant impact on the formation and development of critical thinking skills among elementary school students in Indonesia. Keywords: Critical Thinking Skill, Problem Based Learning,  Students Critical Thinking